2014
DOI: 10.1108/amhid-12-2013-0067
|View full text |Cite
|
Sign up to set email alerts
|

The role of prospective screening in the diagnosis of dementia in people with Down's syndrome

Abstract: Purpose -People with Down's syndrome are at increased risk of developing early onset Alzheimer's disease. It has been recommended that all adults with Down's syndrome receive baseline neuropsychological testing for dementia. In certain areas prospective screening of people with Down's syndrome takes place to ensure the early diagnosis of the condition. However, little has been published on the value of this type of screening. The purpose of this paper is to report on a prospective screening programme and asks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These tend to focus on the practicalities of establishing services and screening strategies (e.g., screening frequency, whether assessments are completed directly with people with learning disabilities or informants). They also discuss issues arising as screening and support are introduced; for example, the importance of a multidisciplinary approach, services working together, caregiver training and awareness‐raising and person‐centred, flexible assessments, the role of screening in identifying additional health and social care needs and increasing screening uptake (Cairns, Lamb, & Smith, ; Hobson et al., ; Jervis & Prinsloo, ; Kalsy et al., ; Starkey, Bevins, & Bonell, ).…”
Section: Introductionmentioning
confidence: 99%
“…These tend to focus on the practicalities of establishing services and screening strategies (e.g., screening frequency, whether assessments are completed directly with people with learning disabilities or informants). They also discuss issues arising as screening and support are introduced; for example, the importance of a multidisciplinary approach, services working together, caregiver training and awareness‐raising and person‐centred, flexible assessments, the role of screening in identifying additional health and social care needs and increasing screening uptake (Cairns, Lamb, & Smith, ; Hobson et al., ; Jervis & Prinsloo, ; Kalsy et al., ; Starkey, Bevins, & Bonell, ).…”
Section: Introductionmentioning
confidence: 99%
“…The population estimate approach can be complemented by reviewing the notes of all individuals diagnosed with dementia to determine the proportion where concerns were first raised during routine screening. This would allow services to identify whether dementia was being picked up during routine screening or from other sources (Starkey et al, 2014 for an example). Other evaluation methods include asking professionals involved in the assessment process (Chapman et al, 2017) and service users about their experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study has evaluated the value of frequent reassessment (Starkey et al, 2014). The authors found that many of the people in the 40-49 age group with a diagnosis of dementia had concerns raised during routine screenings, which were conducted once every two years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation